Elevated placenta growth factor levels in the early second-trimester amniotic fluid are associated with preterm delivery. (17th October 2016) - Lee, Hambak; Kwon, Ji Young; Lee, Seungok; Kim, Sa Jin; Shin, Jong Chul; Park, In Yang
Abstract: Objective : The purpose of this study was to determine how angiogenesis-related factors correlate with preterm delivery. Methods : A cohort of 382 pregnant women undergoing early second-trimester genetic amniocentesis was enrolled and followed-up until delivery, and the amniotic fluid was collected and stored as a nested case-control study. Cases with preterm delivery ( n = 31) were compared with matched controls with term delivery ( n = 62). The amniotic fluid concentrations of placenta growth factor (PlGF), angiogenins, angiopoietin-2, soluble fms-like tyrosine kinase and soluble endoglin were determined using enzyme-linked immunosorbent assays. Results : Women who delivered preterm had a higher amniotic PlGF concentration compared with the control group (median 12.6 pg/ml versus 6.1 pg/ml; p =0.027). Other angiogenesis-related factors did not show any differences between case and control groups. The odds ratio for preterm delivery based on amniotic fluid PlGF was 1.031 (95% confidence interval: 1.002–1.061; p =0.035). Additionally, when the cases were subdivided into early preterm, late preterm and term groups, PlGF values between the early preterm and term delivery groups were significantly different (median 16.6 pg/ml versus 6.1 pg/ml; Bonferroni-adjusted p =0.018). Conclusion : Amniotic fluid PlGF levels in the early second trimester of pregnancy are associated with preterm delivery.